2017
DOI: 10.32404/rean.v4i5.2210
|View full text |Cite
|
Sign up to set email alerts
|

Monitoramento De Variáveis Micrometeorológicas Em Diferentes Ambientes Protegidos No Período De Inverno

Abstract: Ambientes distintos podem exercer influência sobre o crescimento e desenvolvimento de mudas devido à diferença entre as variáveis micrometeorológicas. Objetivou-se desta forma, monitorar e comparar as variáveis micrometeorológicas no interior de ambientes protegidos, na Universidade Estadual de Mato Grosso do Sul, Unidade Universitária de Cassilândia, MS, no período de 28 de junho a 27 de agosto de 2017. Os ambientes avaliados foram: 1. estufa agrícola coberta com filme de polietileno com tela lateral e fronta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
2
6
0
2
Order By: Relevance
“…The mean temperature and relative humidity recorded in the production environments, during the experiment, were 25.7 ºC and 72 %, respectively (Figure 1). These environmental conditions are similar to the values reported by Paula et al (2017), who also found differences only for solar radiation data, when comparing protected and non-protected environments.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The mean temperature and relative humidity recorded in the production environments, during the experiment, were 25.7 ºC and 72 %, respectively (Figure 1). These environmental conditions are similar to the values reported by Paula et al (2017), who also found differences only for solar radiation data, when comparing protected and non-protected environments.…”
Section: Resultssupporting
confidence: 89%
“…Screenhouses and greenhouses are examples of the seedling production environments that can provide micrometeorological conditions capable of improving the plant growth and quality (Darezzo et al 2004, Costa et al 2012. Thus, the light intensity and temperature within the seedling production environment may be limited (Paula et al 2017), preventing abiotic stresses that may cause excessive evapotranspiration, photosynthetic capacity inhibition and impaired plant growth and development (Araújo & Deminicis 2009, Taiz & Zeiger 2013. The understanding of the types of production environment, covering material, color and shading level of the screen, among other factors, aims to identify the best environment that optimizes the growth potential of the plants.…”
mentioning
confidence: 99%
“…Há evidências de que o uso de cobertura com filme plástico ou com telados sobre cultivos agrícolas promovem modificações no microclima do ambiente, especialmente devido as alterações na transmissividade da radiação solar. (FERREIRA et al, 2004;LULU;PEDRO JR., 2006;PEDRO JR. et al, 2011;PAULA et al, 2017;SILVA et al, 2021).…”
Section: Introductionunclassified
“…O uso de coberturas sobre os cultivos permite proteção às plantas, por exemplo, contra alta intensidade de radiação solar durante todo o seu crescimento. Contudo, mudanças de temperatura, umidade relativa do ar e radiação solar (FERREIRA et al, v.21 n.3 2022(FERREIRA et al, v.21 n.3 2004PAULA et al, 2017;SILVA et al, 2021) podem alterar a composição e a qualidade do fruto. (SCHIEDECK et al, 1999;REIS et al, 2012).…”
Section: Introductionunclassified
“…These studies often involved energy balance, radiation and/or mass balance, such as the environmental modification caused by low perforated polyethylene tunnels in lettuce growth (Buriol et al, 1993a), the meteorological elements in a plastic greenhouse in Pelotas-RS (Camacho et al, 1995), the protected cultivation and microclimatic aspects (Sentelhas and Santos, 1995), the energy balance in pepper plants under protected and field cultivation (Cunha et al, 2001), the energy balance in the cucumber crop in a natural and protected environment , the radiation balance and heat flux in the soil in a natural and protected environment with cucumber cultivation , the estimation of the latent heat flux by the energy balance in pepper protected cultivation (Cunha et al, 2002), the micrometeorological alterations caused by the plastic greenhouse and its effects on the pepper crop growth and production (Cunha and Escobedo, 2003 ), the use of meshes and shading in a protected environment and on the growth and commercial production of Gerbera jamesonii (Guiselini et al, 2004a), the effect of the protected environment cultivated with melon on the meteorological elements and its relationship with external conditions (Vásquez et al, 2005), the microclimate of vineyards cultivated under plastic cover and full sun (Lulu e Pedro Júnior, 2006), the microclimatic characterization of coffee trees cultivated under shading mesh and in full sun (Morais et al, 2007), the study of microclimate simulations in greenhouses aiming at the acclimatization of micropropagated banana plantlets cv Grande Naine (Scaranari et al, 2008), micrometeorological changes in vineyards by using plastic covers (Cardoso et al, 2008), the management of solar radiation coverage of protected environments and its effects on gerbera production (Guiselini et al, 2010), models for estimating micrometeorological elements in a protected environment (Costa et al, 2011), the efficiency of heat-reflective and shading screens in a screen-like protected environment under high temperatures (Rampazzo et al, 2014), agricultural screens as an undercover in the cultivation of hydroponic lettuce (Sales et al, 2014), the use of thermoreflective screen in protected environments for tomato cultivation (Ferrari and Leal, 2015), solar radiation and air temperature in a protected environment (Rebouças et al, 2015) and the monitoring of micrometeorological variables in different protected environments in the winter period ( Paula et al, 2017).…”
Section: Introductionmentioning
confidence: 99%